Integration of Ultrasound in Undergraduate Medical Education at the California Medical Schools: A Discussion of Common Challenges and Strategies From the UMeCali Experience. (13th January 2016) - Chiem, Alan T.; Soucy, Zachary; Dinh, Vi Am; Chilstrom, Mikaela; Gharahbaghian, Laleh; Shah, Virag; Medak, Anthony; Nagdev, Arun; Jang, Timothy; Stark, Elena; Hussain, Aliasgher; Lobo, Viveta; et al.
Abstract : Since the first medical student ultrasound electives became available more than a decade ago, ultrasound in undergraduate medical education has gained increasing popularity. More than a dozen medical schools have fully integrated ultrasound education in their curricula, with several dozen more institutions planning to follow suit. Starting in June 2012, a working group of emergency ultrasound faculty at the California medical schools began to meet to discuss barriers as well as innovative approaches to implementing ultrasound education in undergraduate medical education. It became clear that an ongoing collaborative could be formed to discuss barriers, exchange ideas, and lend support for this initiative. The group, termed Ultrasound in Medical Education, California (UMeCali), was formed with 2 main goals: to exchange ideas and resources in facilitating ultrasound education and to develop a white paper to discuss our experiences. Five common themes integral to successful ultrasound education in undergraduate medical education are discussed in this article: (1) initiating an ultrasound education program; (2) the role of medical student involvement; (3) integration of ultrasound in the preclinical years; (4) developing longitudinal ultrasound education; and (5) addressing competency.